The vertebral curvature of sportsmen - Uetake, T.; Ohtsuki, F.; Tanaka, H.; Shindo, M. (Journal of Sports Sciences, 1998)
To characterize the vertebral curvature of individuals from a variety of sporting backgrounds, 380 Japanese males were categorized into 11 groups based on sport participation: rugby, soccer, kendo, swimming, sailing, four track and field events (sprinting, distance running, jumping and throwing), bodybuilding and no athletic engagement. The vertebral curvature of each subject was estimated from a Moire photograph. The vertebral curvature lines of the 11 groups were compared and classified into four types based on the shape of the vertebral curvature: (1) bodybuilders and swimmers; (2) rugby players, sailors, soccer players and non-athletes; (3) kendo participants, middle- and long-distance runners and sprinters; (4) throwers. The relationship between the shape of the vertebral curvature and the characteristics of the sport was determined. We found that posture was specific to the sport. Sprinters, middle-and long-distance runners, jumpers, kendo participants and throwers had a deeply curved vertebral column, whereas swimmers, bodybuilders, sailors, soccer players, rugby players and non-athletes had a shallow curvature.